FDI Inflows, Employment Generation and Poverty Reduction in ECOWAS Sub Region: A Panel Granger Causality Approach - Adelowokan, Oluwaseyi Adedayo; Omitogun, Olawunmi; Aderemi, Timothy Ayomitunde (EuroEconomica, 2023)
The aim of this study is to examine interaction among FDI, employment generation and poverty reduction in ECOWAS sub region over the periods of 1990 to 2019. Despite the fact that past studies have established the linkages among FDI inflows, employment and poverty ameiloration in various economies, yet the dynamic relationship among these variables has been ignored in developing countries, especially ECOWAS Sub-Region. To this end we estimated causal relationship, Pairwise Dumitrescu Hurlin Panel Causality Tests.. The results of the causal relationship state that poverty reduction in terms of human capacity development is a critical variable stimulating employment generation and FDI inflows in ECOWAS sub region in the past three decade. Arising from the study`s findings, the following vital policy recommendations are made for policymakers in ECOWAS sub region in particular and other developing countries in Africa and beyond in general that employment generation should be considered as an urgent policy whenever policymakers desire to raise the level of FDI inflows and poverty reduction in the sub region.